KAJIAN APLIKASI E-GOVERNMENT DALAM PENERAPAN IDENTITAS KEPENDUDUKAN DIGITAL DI KOTA SURABAYA (STUDI KASUS KECAMATAN SEMAMPIR) - Wati, Lisa Sintha; Pradana, Galih Wahyu (Universitas Negeri Surabaya, 2024)
PANRB Ministerial Regulation No. 91 of 2021 provides guidance on public service innovation within ministries or institutions, local governments, BUMN, and BUMD. One example of innovation in the realm of e-government in Indonesia today is the change from Electronic KTP to Digital KTP. The change from KTP-El to Digital KTP is accompanied by a considerable financial increase because it is no longer necessary to produce or distribute KTP blanks. The purpose of innovation is to increase the reliability and security of data collection while improving public services, namely making it easier for people to carry digital ID cards and update in real time, the purpose of this research is to find out the Implementation of E-government through the Implementation of the Digital Population Identity Application Program in Semampir District because it is one of the most populous sub-districts with the lowest IKD activation. The research method used is descriptive with a qualitative approach, based on the identification of success factors for e-government implementation according to Maulidhia, J. P. (2020). Data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing. The results of the study, the role of the leader has been carried out well, so that employees feel responsible for their duties. Stakeholders, Semampir Sub-district has collaborated with the government sector quite well but with the private sector has not been able to work together. In terms of human resources, service employees are very adaptable to technology, financial resources, Semampir Sub-district proposes a budget related to wifi and computer maintenance, technology and information are needed to add SIAK computers to reduce long queues for IKD activation, in terms of the process of implementing e-government through digital population identity in Semampir Sub-district has an evaluation of the challenges faced and effective strategies to overcome them, in terms of goals and values need to consider the maximum benefits for all communities, in terms of regulations and government policies are quite responsive regarding questions about regulations.